Pedestrian pathways along Tunjungan Street, Surabaya (ARTEKS : Jurnal Teknik Arsitektur, 2026)
This study seeks to investigate the functioning of pedestrian urban spaces as components of threshold environments, grounded in the theoretical framework of urban interiority. It addresses issues and phenomena associated with the use of pedestrian spaces, not solely as corridors for movement but as dynamic settings that accommodate diverse forms of urban social interaction. The research aims to clarify how threshold spaces operate as spatial mechanisms that enable social activities within the context of urban interiority. Utilizing a qualitative case study method, this research concentrates on the Tunjungan Corridor, a prominent street in Surabaya, to illustrate the ambiguous condition of the threshold between interior and exterior urban spaces as a unified spatial experience. The study involves mapping and drawing several segments of pedestrian space to demonstrate the emergence of threshold spaces as integral components of urban interiority. The findings offer a nuanced interpretation of the spatial operations of pedestrian environments as threshold spaces, examined through five principal elements: spatial design, spatial function, spatial definition, spatial structure (form and order), and spatial sequence. These findings contribute to a broader understanding of space design grounded in urban interiority and provide a reference framework for future spatial operations in pedestrian-oriented design.
Keywords: Pedestrian ways; Threshold space; Tunjungan Street Surabaya; Urban interiority